2015
DOI: 10.1002/ijop.12231
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity as a precedent factor for problematic Internet use: How can we be sure?

Abstract: Previous research has suggested that problematic Internet use (PIU) is associated with impulse control disorder. Although researchers have suggested that impulsivity is a risk factor for PIU, the literature lacks longitudinal evidence on the relationship between impulsivity and PIU. We aimed to use a cross-lagged analytic framework to identify temporal order effects and hypothesised that impulsivity was the precedent factor for PIU. In a panel sample of college students (N = 367), trait impulsivity and PIU wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 24 publications
4
20
1
Order By: Relevance
“…Taken together, it can be assumed that gender can be a moderator of the relationship between impulsivity and problematic behavior as well as and life satisfaction and problematic behaviors such as PVG and PFU. However, previous studies [88][89][90][91][92][93][94][95] have reported a non-consistent pattern of gender differences in these relationships. Consequently, it is important to understand the differences between males and females in the relationship between impulsivity and problematic behavior as well as life satisfaction and these types of behaviors.…”
Section: Gender Perspectivementioning
confidence: 76%
See 3 more Smart Citations
“…Taken together, it can be assumed that gender can be a moderator of the relationship between impulsivity and problematic behavior as well as and life satisfaction and problematic behaviors such as PVG and PFU. However, previous studies [88][89][90][91][92][93][94][95] have reported a non-consistent pattern of gender differences in these relationships. Consequently, it is important to understand the differences between males and females in the relationship between impulsivity and problematic behavior as well as life satisfaction and these types of behaviors.…”
Section: Gender Perspectivementioning
confidence: 76%
“…Similarly, Shokri, Potenza and Sanaeepour [92] postulated similar relationships between problematic Internet use and impulsivity traits such as negative urgency, positive urgency, lack of perseverance, sensation seeking lack of premeditation across gender. However, Chen, Lo and Lin [93] reported a positive relationship between motor impulsivity and problematic internet use among females, whereas no similar relationship was found among males. In this context, it should be noted that Cross, Copping and Campbell [94] reported that males had a higher level of attentional, motor, non-planning, and perseverance impulsivity than females in meta-analysis of 56 studies.…”
Section: Gender Perspectivementioning
confidence: 85%
See 2 more Smart Citations
“…Finally, it is important to consider the role that inhibition may have in PIU. In fact, studies have reported that PIU is related to higher scores on self-report measures of impulsivity, which is theoretically orthogonal to BIS/BAS function (Cao, 2007;Chen et al, 2017;Franken and Muris, 2006;Mottram, 2009). Impulsivity is a key feature of many addictive behaviors, and yet it does not always relate to BAS learning of reward expectancies or behavioral responses to rewarding stimuli (Corr, 2004;Ding et al, 2014;Lee et al, 2012;Shapira et al, 2000).…”
Section: Introductionmentioning
confidence: 99%